Biodegradable gelatin/pullulan aerogel modified by a green strategy: Characterization and antimicrobial activity. (December 2022) - Yang, Zhichao; Shen, Chaoyi; Rao, Jingshan; Li, Jiawen; Yang, Xiangzheng; Zhang, Hui; Li, Jiangkuo; Fawole, Olaniyi Amos; Wu, Di; Chen, Kunsong
Abstract: The practical application of products prepared on the basis of gelatin (GA) or pullulan (PUL) is greatly limited by their solubility in aqueous solutions and relatively poor mechanical properties. Therefore, modification by chemical cross-linking agents is often needed. However, chemical residues and cytotoxicity limit its application in the food industry. The Maillard reaction, as a green cross-linking method, can be a suitable solution to this problem. In this work, biodegradable GA/PUL composite aerogels were fabricated by a freeze-drying method, and the Maillard reaction was used as a green modification strategy to improve the mechanical properties and solubility resistance of GA/PUL aerogels. The results showed that the Maillard reaction significantly enhanced the water resistance of the GA/PUL composite bioaerogel, resulting in an increase in the water contact angle from 57.45°− 86.42–98.93°− 116.05° at 60 s. In addition, the modified GA/PUL composite bioaerogel had a compression resistance of 1.76–3.01 MPa at a strain of 20 % and thermal insulation properties of 0.064–0.070 W/m∙K, and was completely biodegradable in 10 days. Moreover, the bioaerogel with nisin exhibited antibacterial activity against E. coli and S. aureus . In conclusion, this work effectively expands the application of gelatin-based bioaerogels in the food packaging industry. Graphical Abstract: ga1 Highlights: Properties were optimized for bioaerogel using a green modification strategy. The water contact angle increased from 57.45°− 86.42–98.93°− 116.05° at 60 s. The thermal conductivity of gelatin/pullulan bioaerogel was 0.064–0.070 W/m∙K. The bioaerogel with nisin could inhibit E. coli and S. aureus. The fabricated gelatin/pullulan bioaerogel was degraded in soil in 10 days.